Growth and Yield of Red Chili at various Doses of Chicken Manure Using Conventional and Floating Cultivation Techniques - Susilawati Susilawati; Irmawati Irmawati; Sri Sukarmi; Muhammad Ammar (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2023)
The aimed of this study was to determine the effect of chicken manure application on red chili plants using conventional and floating cultivation techniques. The research was carried out on the experimental farm for conventional cultivation techniques and in research pond for floating cultivation located in the Faculty of Agriculture, Sriwijaya University, Indralaya Campus, Ogan Ilir, South Sumatra with an altitude of 10 m above sea level from July to November 2022. The experiment used a randomized block design with one factor, namely chicken manure (0, 10, 20 and 30 tons/ha) with three replications. While the floating experiment used 200 cm x 100 cm of bamboo rafts. Parameters observed included plant height, number of leaves, crown diameter, fruit length, fruit diameter, fruit weight per fruit, and total fruit weight per plant. Data were analyzed using Analysis of Variance (ANOVA) at the 5% level. The results showed that increasing the dose of chicken manure up to 30 tons/ha in both cultivation techniques increased plant height and number of leaves. Likewise for the number and weight of fruit, obtained at the same dose in conventional techniques, namely 30 tons/ha. However, fruit length and diameter parameters were higher in floating cultivation at all doses of chicken manure treatments. Therefore, it was concluded that the use of chicken manure could increase the growth of chili plants in both cultivation techniques, although the size of the polybags used could not support the growth and yields optimally.